Analysis of Video Signal Transmission Through DWDM Network Based on a Quality Check Algorithm - Ilic, S.; Jaksic, B.; Petrovic, M.; Markovic, A.; Elcic, V. (Engineering, Technology & Applied Science Research, 2013)
This paper provides an analysis of the multiplexed video signal transmission through the Dense Wavelength Division Multiplexing (DWDM) network based on a quality check algorithm, which determines where the interruption of the transmission quality starts. On the basis of this algorithm, simulations of transmission for specific values of fiber parameters ​​ are executed. The analysis of the results shows how the BER and Q-factor change depends on the length of the fiber, i.e. on the number of amplifiers, and what kind of an effect the number of multiplexed channels and the flow rate per channel have on a transmited signals. Analysis of DWDM systems is performed in the software package OptiSystem 7.0, which is designed for systems with flow rates of 2.5 Gb/s and 10 Gb/s per channel.